INITIATIVES OF THE MUNICIPAL LEGISLATIVE POWER IN PROMOTING THE RIGHT TO POLITICAL PARTICIPATION - Sidney Cassoli, Ráriton (Revista Gênero e Interdisciplinaridade, 2024)
This paper aims to demonstrate the importance of the municipal legislative power in the context of low political engagement in the country. It shows how civic education regarding political knowledge, through the involvement of the school community – teachers, coordinators, principals, and students – can be a pathway to raising awareness about the importance of popular participation in the political context of the municipality and the country, as well as in the defense of fundamental rights.